Putting Knowledge to Work and Letting Information Play - Luke, Timothy W.; Hunsinger, Jeremy; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
These collected papers are critical reflections about the rapid digitalization of discourse and culture. This disruptive change in communicative interaction has swept rapidly through major universities, nation states, learned disciplines, leading businesses, and government agencies during the past decade. To commemorate the tenth anniversary of the Center for Digital Discourse and Culture (CDDC) at Virginia Tech, which has been a pioneering leader for many of these changes in university settings, the contributors to this volume examine the transformative implications of digitalizing discourse and culture inside and outside of the academic arena. These technologies of digitalization have created new communities of users, which are highly engaged with their new communicative possibilities, informational content, and discursive forms. Few have asked what these changes will mean, and many of the most important voices engaged in debates about this critical transformation are gathered here in this volume. Each author in his or her own way considers what accepting digital discourse and informational culture now means for contemporary economies, governments, and societies.
Keywords: Education; Education; Education (general).